Indian Journal of Chemistry- A - Council of Scientific & Industrial Research (India); Indian National Science Academy; National Institute of Science Communication and Information Resources (New Delhi, India) (New Delhi CSIR, 1963)
Print only.
Title from cover.
Keywords: Chemistry -- Periodicals; Chemistry, Analytic -- Periodicals; Chemistry, Inorganic -- Periodicals; Chemistry, Physical and theoretical -- Periodicals; Chemistry, Analytical -- Periodicals; Chemistry, Inorganic -- Periodicals; Chemistry, Physical -- Periodicals